A comparative study of sex difference in calbindin neurons among mice, musk shrews, and Japanese quails. (19th September 2016) - Moe, Yadanar; Tanaka, Tomoko; Morishita, Masahiro; Ohata, Ryoko; Nakahara, Chihiro; Kawashima, Takaharu; Maekawa, Fumihiko; Sakata, Ichiro; Sakai, Takafumi; Tsukahara, Shinji
Highlights: The MPN and BNST of mice contain SDNs composed of calbindin neurons. The MPN of musk shrews contains a SDN composed of calbindin neurons. The BNST of musk shrews contains a SDN composed of non-calbindin neurons. Calbindin neruons in the MPN and BNST of Japanese quails were small in number. Abstract: The medial preoptic nucleus (MPN) and the bed nucleus of the stria terminalis (BNST) of mice contain sexually dimorphic nuclei (SDNs) that are larger and have more neurons expressing calbindin D-28K (CB), a calcium-binding protein, in males than females. However, it is largely unknown whether such SDNs exist in species other than rodents. In this study, we performed an immunohistochemical study of CB in the MPN and BNST of musk shrews and Japanese quails to examine the existence of homologs of SDNs in mice. Like mice, musk shrews had a SDN exhibiting male-biased sex differences in volume and CB-immunoreactive (ir) cell number in the MPN. The BNST of musk shrews also contained a male-biased SDN, but consisted of non-CB neurons. The paratenial thalamic nucleus of musk shrews, but not mice, had more CB-ir cells in males than females. In Japanese quails of both sexes, CB-ir cells in the MPN and BNST were extremely small in number and did not cluster. These results suggest that the distribution of CB neurons differs among these species. Musk shrews may have a homolog of the SDN composed of CB neurons in the MPN of mice.